PENGUATAN LITERASI AWAL MELALUI POJOK BACA PADA ANAK USIA 5-6 TAHUN DI TK PERTIWI 14.26.11 DESA GIYANTI - Sutinah; Lina Putriyanti (STKIP Subang, 2024)
This research aims to examine activities related to strengthening early literacy in Early Childhood Education, namely in Kindergarten. This research uses a qualitative descriptive research type. The data collection techniques used were observation, interviews and documentation studies on children aged 5-6 years at the Pertiwi Kindergarten (TK) 14.26.11 Giyanti Village, Rowokele District, Kebumen Regency. The instruments used were observation sheets, interview sheets and documentation studies related to activities to strengthen early literacy at Pertiwi Kindergarten 14.26.11 Giyanti Village through reading corner services. Reading corner services at Pertiwi Kindergarten 14.26.11 were carried out with various activities. In general, reading corner service activities can develop and strengthen early literacy skills in Pertiwi Kindergarten 14.26.11 Giyanti Village.